Інфраструктурне забезпечення капіталізації земельних ресурсів - Сакаль, О.В. (Економіка природокористування і охорони довкілля, 2014)
Проаналізовано зміст поняття капіталізація земель та фактори, що визначають міру капіталізації земельних ресурсів. Обґрунтовано основні напрями підвищення ролі ринкової інфраструктури щодо розвитку земельного капіталу. У зв’язку з цим
визначено сутність інфраструктурного забезпечення капіталізації земельних ресурсів. Доведено, що інфраструктурне забезпечення капіталізації земельних ресурсів є складовою ринкової інфраструктури національної економіки України, тому ефективність капіталізації земель зумовлюється їх інтеграцією. Набули подальшого розвитку теоретико-методологічні засади управління суспільними відносинами щодо земель у частині ідентифікації інфраструктурного забезпечення капіталізації земельних ресурсів. На етапі формування земельного капіталу інфраструктурне забезпечення капіталізації земельних ресурсів покликане виконувати
організаційно-впорядковуючу функцію, тоді як на етапі функціонування землі як активу воно підтримує сталість зв’язків системи. Визначено складові підсистем інфраструктурного забезпечення капіталізації земель із виділенням учасників відносин щодо володіння й обігу прав власності та користування земельними ресурсами. Блоковий склад інфраструктурного забезпечення капіталізації земельних ресурсів представлений такими підсистемами: нормативно-регулятивна, організаційно-технічна, фінансово-кредитна, науково-освітнє та інформаційне забезпечення. The content of the concept of capitalization of land, as well as factors determining the extent of capitalization of land resources, are analysed. The main trends of increasing the role of market infrastructure as to development of land capital are substantiated. In this connection, the essence of the infrastructural ensuring of the capitalization of land resources is defined. It is proved that the infrastructural ensuring of capitalization of land resources is a part of the market infrastructure of Ukrainian national economy, that is why the capitalization of lands is predetermined by their integration. The theoretical and methodological bases of public relations management concerning the lands in the
identification of infrastructural ensuring of capitalization of land resources were developed. At the stage of formation of land capital, the infrastructural ensuring of land resources capitalization is called to perform organizational and ordering function, while in the phase of land functioning as the asset, it supports the sustainability of system’s communications. The constituents of the sub-systems of the infrastructural ensuring of capitalization of lands with separation of participants of relations as to ownership and circulation of property rights and use of land resources were defined. Block composition of infrastructural ensuring of capitalization of land resources is represented by the following
subsystems: normative and regulatory, organizational and technical, financial and credit, research and educational and informational support. Infrastructural ensuring of capitalization of land resources concerns the rules, processes, owners and institution – decision makers on land and provides in particular, a partnership of public authorities at the appropriate level and local owners of rights owning and using the land parcels, protection of their rights on profit, responsibility for the environmental, economic and social consequences of administrative decisions on land and other stakeholders (external to the territory or region investors), sustainable use of land and other natural resources,
supporting local communities to promote the development of rural and other disadvantaged districts, creating favourable conditions for development
and strengthening of local manufacture, social and economic growth. The above mentioned will serve as a basis for further research of externalities capitalization of land resources and justification of mechanisms of their internalization.